Dois romances distópicos e satíricos - doi: 10.4025/actascilangcult.v33i1.10059 - Bonnici, Thomas (Acta Scientiarum. Language and Culture, 2011)
EVARISTO, Bernardine. Blonde roots. London: Penguin, 2009, 261 p. ISBN 9780141031521. LEVY, Andrea. The long song. New York: Farrar, Straus and Giroux, 2010, 313 p. ISBN 9780374192174.